2009
DOI: 10.1038/jid.2008.458
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Cε Inhibits UVR-Induced Expression of FADD, an Adaptor Protein, Linked to both Fas- and TNFR1-Mediated Apoptosis

Abstract: PKCε overexpression in FVB/N transgenic mice sensitized skin to ultraviolet radiation (UVR)-induced development of squamous cell carcinomas (SCC) (Wheeler et al., 2004; Wheeler et al., 2005) and suppressed formation of sunburn cells, which are DNA-damaged keratinocytes undergoing apoptosis (Wheeler et al., 2004). Here, we elucidated the mechanisms associated with inhibition of UVR-induced appearance of sunburn cells in PKCε transgenic mice. We found that the inhibition of UVR-induced sunburn cell formation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…It is important to understand that programmed cell death of UV-damaged skin cells is a definitive cancer-preventing pathway. Transgenic animals designed to be resistant to the development of UV-induced sunburn cells can tolerate more UV radiation without burning, but they are predisposed to developing skin cancers [5, 12]. …”
Section: Uv Radiation Causes Dna Damage Apoptosis and Release Of Autmentioning
confidence: 99%
“…It is important to understand that programmed cell death of UV-damaged skin cells is a definitive cancer-preventing pathway. Transgenic animals designed to be resistant to the development of UV-induced sunburn cells can tolerate more UV radiation without burning, but they are predisposed to developing skin cancers [5, 12]. …”
Section: Uv Radiation Causes Dna Damage Apoptosis and Release Of Autmentioning
confidence: 99%
“…Apoptosis is characterized by a number of well-defined features, including phosphatidyserine exposure, membrane blabbing, activation of caspase, chromatin condensation and DNA fragmentation (15). Classical apoptosis may proceed by the intrinsic and/or extrinsic pathway (16)(17)(18). In the intrinsic pathway, mitochondria are induced to release a number of factors, leading to the formation of the apoptosome, which is comprised of the adapter protein Apaf-1, cytochrome c and caspase-9 (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DAPK1 and DAPK2 show similarities in their regulation of kinase activity within the catalytic structural domain and both show the following two aspects: 1 ) upon Ser308 dephosphorylation, calcium-activated CaM binds to the self-regulated/CaM-bound fragment pulling the structural domain out of the catalytic cleft; 2 ) simultaneously, CaM binding promotes the dephosphorylation of Ser308 ( Shoval et al, 2011 ; Simon et al, 2016 ), and the dephosphorylated Ser308 increases the DAPK2 activity by promoting dimerization like the dephosphorylated Ser318; therefore, the binding of CaM and the dephosphorylation of Ser308 are reciprocal. In addition, a number of studies have confirmed this role of Ser308 in DAPK1 and DAPK2, replacing all Ser308 in both kinases with Ala or deleting the CaM-binding region in both kinases to produce constitutively active kinases that exhibit more potent killing and non-Ca-dependent catalytic activity ( Bialik and Kimchi, 2006 ; Aziz et al, 2009 ). In addition to an N-terminal catalytic domain that is 83% homologous to DAPK1, DAPK3 also has a nuclear localization signal (NLS) sequence and a leucine zipper domain at the C-terminus (427–441).…”
Section: The Structure Of Dapkmentioning
confidence: 97%